2006
DOI: 10.3748/wjg.v12.i26.4237
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on correlation between expression of CD58 molecule and severity of hepatitis B

Abstract: The level of CD58 molecule (in both serum and PBMC form) of patients with hepatitis B is related to the degree of liver damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The expression of CD58 in hepatocytes of chronic hepatitis exhibits cytoplasmic and membranous staining and elevated with the severity of chronic HBV infection, the degree of inflammatory activity, and liver damage ( 177 179 ). More importantly, the proportion of CD58 + cells in peripheral blood mononuclear cells and the levels of sCD58 in serum of patients with HBV infection are conspicuously higher than that in the healthy individuals and positively associated with serum levels of AST and ALT ( 178 , 179 ). These findings demonstrate that CD2-CD58 interactions between lymphocytes and hepatocytes exert an essential function in chronic hepatitis ( 177 ).…”
Section: Chronic Hepatitismentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of CD58 in hepatocytes of chronic hepatitis exhibits cytoplasmic and membranous staining and elevated with the severity of chronic HBV infection, the degree of inflammatory activity, and liver damage ( 177 179 ). More importantly, the proportion of CD58 + cells in peripheral blood mononuclear cells and the levels of sCD58 in serum of patients with HBV infection are conspicuously higher than that in the healthy individuals and positively associated with serum levels of AST and ALT ( 178 , 179 ). These findings demonstrate that CD2-CD58 interactions between lymphocytes and hepatocytes exert an essential function in chronic hepatitis ( 177 ).…”
Section: Chronic Hepatitismentioning
confidence: 99%
“…Immune adhesion molecule CD58 may strengthen viral elimination via activating T/NK cells and stimulating the cytotoxic immune response. Unfortunately, this also causes the damage of hepatocytes ( 179 ).…”
Section: Chronic Hepatitismentioning
confidence: 99%
“…The previous study suggested that sCD58 levels in the serum of HBV-infected patients are substantially higher than in the normal population and correlate with disease severity [ 47 ]. The majority of HCC occurs in the presence of chronic liver disease and cirrhosis, for which hepatitis is the leading cause [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed on the surface of B cells, T cells, monocytes, granulocytes and thymic epithelial cells. It is an important adhesion molecule in cells [20,21]. The ligand of CD58, CD2, also known as T11 and LFA-2, is the erythrocyte (E) rosette receptor.…”
Section: Introductionmentioning
confidence: 99%